Are farm input subsidies a disincentive for integrated pest management adoption? evidence from Zambia - Tambo, J.A.; Liverpool-Tasie, L.S.O. (Wiley, 2024)
Input subsidy programmes (ISPs) remain a popular but contentious policy tool to promote agricultural intensification, food security and poverty reduction across Africa. Although previous studies have explored the impact of ISPs on various smallholder outcomes, no studies have analysed the impact of recent ISPs on pest management. This is particularly important given the increasing pest challenges due to climate change and the recent surge in pesticide use in low-income countries and its associated negative consequences for human and environmental health. Thus, this study assessed the effects of ISPs on smallholder adoption of sustainable pest management practices, using data from 1048 smallholder maize plots across major maize-producing zones of Zambia and a control function regression approach. We find consistent evidence that input subsidy receipt is negatively associated with smallholders' adoption of environmentally friendly and sustainable pest management strategies. Participation in the Zambia ISP (particularly the flexible e-voucher system) encourages synthetic pesticide use, at the expense of sustainable practices. We also find that farmers consider synthetic pesticides and biopesticides as substitutes and are more likely to adopt sustainable pest management when they have tenure security and access to financial resources. Given the human and environmental health consequences associated with synthetic pesticide use, it would be important to leverage input subsidy schemes to promote the adoption of safer and more sustainable alternatives to synthetic pesticides. Beyond input subsidies, policies that improve tenure security and financial access for smallholders can promote the adoption of sustainable pest management practices.